Avtomatski merilniki krvnega tlaka za domačo uporabo - ali jim lahko zaupamo? - Geršak, Gregor (Zdravniški vestnik, 2009)
Background This paper describes current state of evaluation of automatic BP devices in Slovenia and internationally. Conclusions In the last decades, non-invasive automatic blood pressure (BP) measurement devices are used with increasing regularity over manual devices. Advantages of automatic (mainly oscillometric) devices over manual mercury-in-glass and aneroid devices are smaller reading error, better reliability and repeatability and lesser environmental hazard. They suffer from larger sensitivity to physiological parameters like arm circumference, arrhythmias and vessel properties. In practice, their main problem is their built-in calculative algorithm which estimates/calculates blood pressure level from pressure pulses in the cuff. Namely, the algorithms are proprietary and hidden, which makes reliable evaluation of devices practically impossible. Evaluation of BP devices is wellresearched and regulated by recommendations, standards and legislation. Like in the majority of countries, the national legislation of the Republic ofSlovenia prescribes the procedures for evaluation of manual and automatic BPmeasurement devices. Procedures include tests in the field of physical quantity of pressure, which are not always applicable to measurement of physiological parameter of blood pressure. While procedures and tests are adequate for the manual BP devices, they are insufficient for the reliable evaluation of the automatic devices. The measuring accuracy of the automatic device is not assessed. The users (patients and physicians) have to trust the accuracy statements (given by the producers or independent institutions) and believe that the device will perform equally reliable despite of all extraneous mechanical and electromagnetic stress factors from environment overits entire life expectancy.
Keywords: avtomatski merilniki; Blood Pressure Determination; Blood Pressure Monitors; Hipertenzija; Hypertension; Krvni pritisk, merilniki; Krvni pritisk, merjenje; krvni tlak; Kvaliteta, nadzor; merilniki; merjenje; natančnost; Oscillometry; Oscilometrija; Quality Control